'Stepchildren of the Ministry': an examination of the difficulties endured by family physicians in Istanbul during the course of the COVID-19 pandemic - Ismail Jan Kara; Adar Eken; Hakan Döndürür; Atakan Arzak; Cansu Yildirim; Seray Basak Bozkurt; Yesim Yasin (CSIRO Publishing, 2022)
IntroductionEfforts to contain the SARS-CoV-2 virus would fall short without strong primary health care. AimIn this study, we aimed to understand family physicians' experiences of coronavirus disease 2019 (COVID-19) in Istanbul, focusing on their coping strategies in order to draw lessons for the future management of pandemics. MethodsTwelve community-based physicians working in Istanbul participated in semi-structured interviews between January and May 2021. Purposive sampling was used to ensure a range of physicians' characteristics. Individual interviews were conducted with each participant on an online platform. Participants were asked 26 open-ended questions. Phenomenological analysis was performed to describe experiences of physicians. ResultsThe physical conditions of participants' health centres were insufficient to provide service safely during the COVID-19 pandemic. Most physicians were uncomfortable about the quality and quantity of personal protective equipment received from the Ministry of Health and took additional measures themselves. Vaccine supply was thought to be insufficient and there were problems with the associated software. Many family physicians highlighted the inadequate communication from the Ministry. Insufficient knowledge about the disease caused anxiety and fear for the physicians and hindered their performance at the beginning of the pandemic. Physicians who live with their families were more anxious than those who did not. DiscussionDespite challenges, routine procedures have mostly been continued, but newly added responsibilities during the COVID-19 pandemic have had significant impact on physicians' lives.